A further investigation of the growth-finance nexus in Kenya - Arayssi, Mahmoud (2018)
This paper focuses on the finance-development nexus investigating the role of financial deepening and trade openness in general and several macroeconomic variables in the economic development of Kenya. Using a vector error-correction model, the paper tries to determine the causal relationships between finance, exports and economic development using a variety of statistical tests in both static and dynamic models. Our finding emphasize the role of financial development and trade openness in improving capital allocation and growth.